Private international law and global governance - Muir Watt, Horatia; e (Oxford : Oxford University Press, 2015)
Taking a critical approach to private international law, this volume examines its function and role in an era of global governance. It asks if private international law has the potential to reassert itself as a significant governance function in respect of new forms of authority beyond the state, and how this might be done.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 14, 2015).
Keywords: Conflict of laws